A Meta-Analysis of Clinical and Echocardiographic Outcomes of Physiological Versus Conventional Pacing - Patrycja Paluszkiewicz; Adrian Martuszewski; Jacek Smereka; Jacek Gajek (Biomedicines)
Background: Conduction system pacing (CSP), encompassing His bundle pacing (HBP) and left bundle branch area pacing (LBBAP), has emerged as an alternative to conventional pacing methods such as right ventricular pacing (RVP) and biventricular pacing (BVP). This meta-analysis aimed to compare the effects of CSP versus conventional pacing on left ventricular function and selected clinical and electrophysiological outcomes. Methods: Prospective and retrospective studies (randomized, observational, registry-based) reporting pre-post data or direct comparisons between CSP (HBP, LBBAP) and conventional methods (BVP, RVP) for at least one of LVEF, LVESV, LVEDV, QRS duration, NYHA class, NT-proBNP, R-wave, or pacing threshold were included. PubMed and Web of Science databases were searched up to 31 March 2025. Quality assessment (QualSyst), publication bias (Egger’s test, trim-and-fill), subgroup analyses, and meta-regression (follow-up duration) were performed. The review was registered in the INPLASY database (INPLASY202540050). Results: 28 studies (8777 patients, 47 comparisons) were included. CSP significantly improved LVEF (SMD = 1.16; 95%CI: 0.94–1.38), shortened QRS duration (SMD = 0.75; 95%CI: 0.24–1.26), and reduced NYHA class (SMD = 1.94; 95%CI: 1.59–2.29), NT-proBNP levels (SMD = 1.27; 95%CI:0.85–1.69), LVEDV (SMD = 0.90; 95%CI: 0.42–1.38), and LVESV (SMD = 1.31; 95%CI: 0.81–1.81). In head-to-head comparisons, LBBAP and HBP showed similar efficacy, both superior to conventional pacing. Improvement in LVEF significantly correlated with longer follow-up (p = 0.004). Publication bias was non-significant (Egger p = 0.15), despite high heterogeneity (I2 > 90%). Conclusions: CSP demonstrated superior clinical and echocardiographic outcomes compared to conventional pacing. Limitations include the predominance of non-randomized studies, high heterogeneity, and variability in follow-up duration, supporting the need for high-quality randomized trials.